1997
DOI: 10.1210/endo.138.10.5572
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Inhibits 20α-Hydroxysteroid Dehydrogenase Expression in the Rat Corpus Luteum through the Glucocorticoid Receptor

Abstract: In this study, we investigated whether progesterone exerts an intraluteal action despite the lack of progesterone receptors (PR) in the rat corpus luteum and whether progesterone acts through the glucocorticoid receptor (GR) to enhance its own levels by down-regulating the expression of 20alpha-hydroxysteroid dehydrogenase (20alpha-HSD). We first established that the corpus luteum constitutively expresses the GR throughout pregnancy and after parturition. We also generated a temperature sensitive SV-40 transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 0 publications
1
22
1
Order By: Relevance
“…Whereas progesterone mediated a reduction in TLR4-and TLR3-induced IL-6 production exclusively through the GR, inhibition of IL-12 production was mediated through the GR and PR. Although it has been shown that glucocorticoids and progesterone can induce upregulation of the anti-inflammatory cytokine IL-10 in human DCs (46), our studies (results not shown) as well as one using rat-derived DCs treated with progesterone did not show an upregulation of IL-10 (47). The timing of LPS treatment relative to the seeding of DC cultures in preparation of stimulation experiments is critical in defining secretion patterns of IL-12 and IL-10 that likely explain the differences between such studies (48).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Whereas progesterone mediated a reduction in TLR4-and TLR3-induced IL-6 production exclusively through the GR, inhibition of IL-12 production was mediated through the GR and PR. Although it has been shown that glucocorticoids and progesterone can induce upregulation of the anti-inflammatory cytokine IL-10 in human DCs (46), our studies (results not shown) as well as one using rat-derived DCs treated with progesterone did not show an upregulation of IL-10 (47). The timing of LPS treatment relative to the seeding of DC cultures in preparation of stimulation experiments is critical in defining secretion patterns of IL-12 and IL-10 that likely explain the differences between such studies (48).…”
Section: Discussioncontrasting
confidence: 79%
“…Progesterone functions by binding to both the GR and PR (44)(45)(46). Using the receptor-specific agonists dexamethasone and norgestrel, we demonstrate in this study the ability of progesterone to differentially use these receptors to cause downregulation of IL-6 and IL-12 production.…”
Section: Discussionmentioning
confidence: 71%
“…Ghahary, 1990;Adesanya et ah, 1996;Clarke et ah, 1997), but downregulates expression of both mRNAs in the rat corpus luteum (Parmer et ah, 1991). A luteal cell line (GG-CL) derived from the large luteal cells of the pregnant rat corpus luteum (Sugino et ah, 1998) (Sugino et al, 1997 and thus the possibility that oestradiol action is mediated by progesterone is eliminated. Another advantage of these cells is that they are responsive to progesterone (Sugino et ah, 1997 (Clayton et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The level of expression of 5a-reductase is upregulated by estradiol and P in the uterus (Minjarez et al 2001) and by 5a-dihydrotestosterone (DHT) in the prostate (Andersson et al 1989, Ji et al 2003. And the expression of 20a-HSO may be altered by P in corpora lutea (Sugino et al 1997) and in endometrial cells (Nakajima et al 2003). These examples suggest that the changes in P-metabolizing enzyme activity/ expression that lead to higher ratios of 5a-pregnane:4-pregnene may be induced by an altered milieu within the breast.…”
Section: J P Wiebe: Progesterone Metabolites In Breast Cancermentioning
confidence: 99%